Y+x=98
y-x=22
I'm going to use elimination.
y+x=98
y-x=22
-----------
2y+0x=120 SIMPLIFY 2y=120 SIMPLIFY y=60.
Substitute that into either equation and you get y=60 and x=38
Have a nice day! :)
Answer:
What are the options?
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
Question
x+5/x+2 - x+1/x²+2x
Answer:
= (x² - 4x - 1)/[x (x+2)]
= (x² - 4x - 1)/[x² + 2x]
Step-by-step explanation:
x + 5/x + 2 - x + 1/x² + 2x
We factorise the second denominator to give us :
x + 5/x + 2 - x + 1/x(x + 2)
We find the L.C.M of both denominators which is x(x+2).
[x(x + 5)-(x + 1)] / (x (x + 2))
Expand the bracket
=[x² +5x - x -1] / [x (x + 2)]
=(x² - 4x - 1) / [x (x + 2)]
= (x² - 4x - 1)/ [x (x + 2)]
= (x² - 4x - 1) / [x² + 2x]
(goh) = 2(x^1/2)-1
(goh)(9) = 2(9^1/2)-1
= 2(3)-1
= 6-1
= 5
(goh)(9) = 5